Cumulative occupational lumbar load and lumbar disc disease – results of a German multi-center case-control study (EPILIFT) - Seidler, Andreas; Bergmann, Annekatrin; Jäger, Matthias; Ellegast, Rolf; Ditchen, Dirk; Elsner, Gine; Grifka, Joachim; Haerting, Johannes; Hofmann, Friedrich; Linhardt, Oliver; Luttmann, Alwin; Michaelis, Martina; et al. (BMC musculoskeletal disorders, 2009)
Background The to date evidence for a dose-response relationship between physical workload and the development of lumbar disc diseases is limited. We therefore investigated the possible etiologic relevance of cumulative occupational lumbar load to lumbar disc diseases in a multi-center case-control study. Methods In four study regions in Germany (Frankfurt/Main, Freiburg, Halle/Saale, Regensburg), patients seeking medical care for pain associated with clinically and radiologically verified lumbar disc herniation (286 males, 278 females) or symptomatic lumbar disc narrowing (145 males, 206 females) were prospectively recruited. Population control subjects (453 males and 448 females) were drawn from the regional population registers. Cases and control subjects were between 25 and 70 years of age. In a structured personal interview, a complete occupational history was elicited to identify subjects with certain minimum workloads. On the basis of job task-specific supplementary surveys performed by technical experts, the situational lumbar load represented by the compressive force at the lumbosacral disc was determined via biomechanical model calculations for any working situation with object handling and load-intensive postures during the total working life. For this analysis, all manual handling of objects of about 5 kilograms or more and postures with trunk inclination of 20 degrees or more are included in the calculation of cumulative lumbar load. Confounder selection was based on biologic plausibility and on the change-in-estimate criterion. Odds ratios (OR) and 95% confidence intervals (CI) were calculated separately for men and women using unconditional logistic regression analysis, adjusted for age, region, and unemployment as major life event (in males) or psychosocial strain at work (in females), respectively. To further elucidate the contribution of past physical workload to the development of lumbar disc diseases, we performed lag-time analyses. Results We found a positive dose-response relationship between cumulative occupational lumbar load and lumbar disc herniation as well as lumbar disc narrowing among men and women. Even past lumbar load seems to contribute to the risk of lumbar disc disease. Conclusion According to our study, cumulative physical workload is related to lumbar disc diseases among men and women.